2016
DOI: 10.1007/s10265-016-0841-0
|View full text |Cite
|
Sign up to set email alerts
|

Early generation of nitric oxide contributes to copper tolerance through reducing oxidative stress and cell death in hulless barley roots

Abstract: The objective of this study was to investigate the specific role of nitric oxide (NO) in the early response of hulless barley roots to copper (Cu) stress. We used the fluorescent probe diaminofluorescein-FM diacetate to establish NO localization, and hydrogen peroxide (H2O2)-special labeling and histochemical procedures for the detection of reactive oxygen species (ROS) in the root apex. An early production of NO was observed in Cu-treated root tips of hulless barley, but the detection of NO levels was decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 70 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Yang-5/Jian-864 through modulation enhanced antioxidant defense, leading to the decreased H 2 O 2 content and the lipid peroxidation of cells. Hu [ 39 ] showed that increasing the concentration of endogenous NO in the roots of Hordeum vulgare cv. Nude, provided by the treatment with SNP (200 µM), was the initial response through the imposition of stress by Cu, modulating the antioxidant defense and reducing the oxidative damage in the roots.…”
Section: Discussionmentioning
confidence: 99%
“…Yang-5/Jian-864 through modulation enhanced antioxidant defense, leading to the decreased H 2 O 2 content and the lipid peroxidation of cells. Hu [ 39 ] showed that increasing the concentration of endogenous NO in the roots of Hordeum vulgare cv. Nude, provided by the treatment with SNP (200 µM), was the initial response through the imposition of stress by Cu, modulating the antioxidant defense and reducing the oxidative damage in the roots.…”
Section: Discussionmentioning
confidence: 99%
“…Metal contamination of waters results in serious environmental problems around the world and are mostly due to human activities, including the use of fertilizers, industrial mining and smelting, as well as the release of urban waste [1]. These metal contaminations are persistent and they can also undergo bio-magnifications and accumulation in food chains [2].…”
Section: Introductionmentioning
confidence: 99%
“…In naked barley (without hull), Cu-tolerance involved nitrate reductase-mediated NO-production (Hu et al, 2015). Further NO-mediated strengthening of antioxidant defense system and the control of oxidative stress and cell death was also shown (Hu, 2016). In Catharanthus roseus, SNP ameliorated Cu-toxicity by decreasing the ROS-burst, promoting the contents of amino acids and the total phenolic in the roots, regulating mineral absorption and re-establishing ATPase activities (Liu et al, 2016).…”
Section: No-mediated Copper-tolerance In Plantsmentioning
confidence: 99%